Pushkin fairy tales and Uzbek children's literature (Journal of Pedagogical Inventions and Practices, 2024)
The article examines the works of the Russian poet, the founder of new Russian literature as well as the prominent representatives of his time A.S. Pushkin's "The Tale of the Fisherman and Fish (Baliqchi va baliq haqida ertak)," along with the outstanding representative of Uzbek children's literature, who delicately expresses the children’s world with humor, the poet T. Adashboev’s work” The tale of golden horse (oltin yolli tulpor)” are relatively analyzed. In addition, the place of these fairy tales in the upbringing of young generation and the importance of its educational aim are paid attention